The discovery of progenetic Allocreadium neotenicum Peters, 1957 (Digenea: Allocreadiidae) in water beetles (Coleoptera: Dytiscidae) in Great Britain - Bray, Rodney A.; Foster, Garth N.; Waeschenbach, Andrea; Littlewood, D Timothy J (Zootaxa, 2012)
Progenetic specimens of Allocreadium neotenicum Peters, 1957 are described from water beetles, Hydroporus rufifrons, an endangered species, and Agabus paludosus from northern England and Scotland, and as non-ovigerous metacercariae from Agabus melanarius from southern England. Morphologically, the worms are identical to A. neotenicum described from water beetles in North America. Molecular phylogenetic estimates based on 28S rDNA sequences show these British specimens as more closely related to the North American freshwater fish parasite Allocreadium lobatum Wallin, 1909 than to the European species A. isoporum (Looss, 1894). A. lobatum shows a predilection for progenesis and may be a senior synonym of A. neotenicum. Based on the molecular phylogeny, the genus Pseudallocreadium Yamaguti, 1971 is considered synonymous with Allocreadium and the two species assigned to that genus, P. neotenicum and P. alloneotenicum (Wootton, 1957) are returned to Allocreadium.